Sosialisasi Pemanfaatan Limbah Sampah Non-Organik Bersama Ibu-Ibu PKK Di RT. 21 Kelurahan Pematang Gubernur - Yuliana, Alisa; Rahmadani, Atiqah; Sari, Masita; Sagita, Nabila Dayana; Mailiza, Nina; Herlin, Herlin; Suwarni, Suwarni; Soleh, Ahmad (LPPM Universitas Dehasen Bengkulu, 2025)
This community engagement activity aimed to increase awareness and practical skills among PKK chairman and residents (Family Welfare Movement) in RT. 21 Pematang Gubernur Subdistrict on managing non-organic household waste. Through participatory methods involving material delivery and hands-on practice, participants were trained to recycle and upcycle waste such as plastic bottles and packaging into useful crafts. The findings showed that participants gained both knowledge and confidence in reusing non-organic waste creatively. The direct engagement model encouraged sustainable behavior change and sparked interest in continuing the craft practice independently at home. The training proved effective in promoting environmental awareness and encouraging household-level waste management innovations.